Religious Concerns on Financial and Psychological Hardship of Cancer Survivors in Eastern Indonesia - Zuardin, Zuardin (Lembaga Junal dan Publikasi, Universitas Muhammadiyah Buton, 2024)
Cancer survivors face significant financial hardship and psychological distress during treatment. This study investigates the role of religiosity as a coping mechanism for cancer survivors experiencing these challenges. Using an explanatory sequential mixed-method approach, the study analyzed data from 817 patients in the quantitative phase and conducted in-depth interviews with 8 informants representing breast, cervical, lung, and prostate cancer. Quantitative findings indicate that 63% of respondents experienced high financial hardship, while 37% faced moderate hardship. Out-of-pocket expenses, including transportation, accommodation, and uncovered medical costs, contributed to these difficulties. Qualitative interviews revealed that financial strain often led to job loss, debt accumulation, and emotional stress, further exacerbating patient challenges. Religiosity emerged as a critical coping strategy, with participants reporting that spiritual practices and reliance on faith provided emotional strength, reduced depression, and enhanced psychological resilience. This study highlights the need for integrated support systems, including expanded insurance coverage, hospital-based spiritual care, and community-driven support programs. The findings contribute to understanding religiosity’s role in managing financial and psychological burdens, particularly in resource-limited settings such as Eastern Indonesia.